Quality of Life in Selected Slum Localities of Varanasi City - Yadav, Sweta; Bilas, Ram (National Geographical Journal of India, 2022)
One of the most enduring physical manifestations of social exclusion in Indian cities is the proliferation of slums and informal settlements. People living in these settlements experience the most deplorable living and environmental conditions, which are characterized by inadequate water supply, squalid conditions of environmental sanitation, breakdown or non-existence of waste disposal arrangements, overcrowded and dilapidated habitation, hazardous location, insecurity of tenure, and vulnerability to serious health risks. Slum residents are also excluded from participating in the economic, social, political and cultural spheres of the city all of which create and nurture capabilities. This paper accounts for variations in socio-economic condition of slums dwellers in Varanasi city. For this purpose a total number of 401 respondents were interviewed by using the structured questionnaire blended with suitable open-ended questions to study their socio-economic conditions, migratory status and other infrastructural studies